2019
DOI: 10.32508/stdj.v22i1.1216
|View full text |Cite
|
Sign up to set email alerts
|

The forming mechanisms of Oligocene combination/stratigraphic traps and their reservoir quality in southeast Cuu Long Basin offshore of Vietnam

Abstract: To date, most of the oil and gas production in Cuu Long Basin (CLB) is contributed from structural traps, making them more and more depleted after years of exploitation. Exploration activities in CLB, therefore, are shifting towards other traps, including stratigraphic and/or combination ones. The results of exploration and appraisal activities in recent years have increasingly discovered more hydrocarbons in the Oligocene section; some of them were discovered in combination/ stratigraphic traps. Many studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Rifting initiated in the Eocene and continued until the end of the Oligocene (Lee et al 2001;Schmidt et al 2003;Hung and Le 2004;Fyhn et al 2009) or the Early Miocene (Cuong and Warren 2009). Nguyen et al (2019) documented two rift periods, a main phase from the Middle Eocene to the Oligocene and a late phase in the Early Miocene. This was followed by an episode of compression in the late Oligocene to Early Miocene (Schmidt et al 2003(Schmidt et al , 2019Hung and Le 2004;Cuong and Warren 2009;Fyhn et al 2009).…”
Section: Regional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifting initiated in the Eocene and continued until the end of the Oligocene (Lee et al 2001;Schmidt et al 2003;Hung and Le 2004;Fyhn et al 2009) or the Early Miocene (Cuong and Warren 2009). Nguyen et al (2019) documented two rift periods, a main phase from the Middle Eocene to the Oligocene and a late phase in the Early Miocene. This was followed by an episode of compression in the late Oligocene to Early Miocene (Schmidt et al 2003(Schmidt et al , 2019Hung and Le 2004;Cuong and Warren 2009;Fyhn et al 2009).…”
Section: Regional Backgroundmentioning
confidence: 99%
“…Schmidt et al (2019) suggested rifting ceased in the mid-Oligocene, followed by inversion in the late Oligocene. The last stage of basin evolution is interpreted as a thermal sag phase beginning in the Early Miocene (Lee et al 2001;Fyhn et al 2009) or Middle Miocene (Cuong and Warren 2009;Nguyen et al 2019). Schmidt et al (2019) noted that none of the faults in the Mekong Delta Fault Zone or in the Cuu Long Basin cut significantly into the adjacent Con Son Swell or into the Nam Con Son Basin.…”
Section: Regional Backgroundmentioning
confidence: 99%
“…The economic success of these traps has spotted the light on these under-explored remains globally (e.g. tight gas in the China Ordos Basin) (Attia et al, 2015;Dolson et al, 2017;Arab et al, 2016;Nguyen et al, 2019;Hall et al, 2019;Sladen and Chiarella, 2020).…”
Section: Implications For Exploring Combined Traps In the Basinmentioning
confidence: 99%
“…Nowadays, cross-plotting approaches based on well-logging data analysis are evaluated as one of the ef-fective methods to determine reservoir properties as well as their other lithological constituents [2,11]. The crossplotting is known as a typical visualization analysis method that is applied in well-logging data interpretation, and to identify or detect anomalies that could be interpreted as the presence of hydrocarbon, fluids, or other lithologies in the reservoirs [12]. Cross-plotting is, therefore, considered as one of the typical methods that can assist in determining the petrophysics properties of reservoirs and the location of the petroleum productcontaining reservoirs [13,14].…”
Section: Introductionmentioning
confidence: 99%